ANALYSIS OF THE EFFECT OF DIAMOND FRAUD IN DETECTING FINANCIAL STATEMENT FRAUD: EMPIRICAL STUDY IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) 2010 – 2017 - Syahputra, Edi (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to determine and analyse the effects of financial targets, financial stability, external pressure, nature of industry, ineffective monitoring, change in auditors, rationalization, and capability, on financial statement fraud simultaneously and partially on manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population in this study are companies that are included in the Manufacturing sector on the Indonesia Stock Exchange (IDX) for the period 2010 - 2017. The samples in this study used Saturated Sampling (Census) techniques, so a population of 139 companies will be taken as a whole sample for 8 consecutive years according to the total observation is 1.112. The results of hypothesis testing prove that financial targets, financial stability, external pressure, nature of industry, ineffective monitoring, change in auditors, rationalization, and capability, simultaneously have a significant effect on financial statement fraud. Partially, financial targets, financial stability, external pressure, nature of industry, ineffective monitoring, rationalization, and capability, have a significant positive effect on financial statement fraud, and change in auditor has a significant negative effect on financial statement fraud.